Summary of the mechanism of ferroptosis regulated by m6A modification in cancer progression - Fan, Bin; Chen, Gangxian; Huang, Shuyi; Li, Ying; Nabil, Zia Ul Haq; Yang, Zuozhang (Frontiers in Cell and Developmental Biology, 2025)
The most common form of internal RNA modification in eukaryotes is called n6-methyladenosine (m6A) methylation. It has become more and more well-known as a research issue in recent years since it alters RNA metabolism and is involved in numerous biological processes. Currently, m6A alteration offers new opportunities in clinical applications and is intimately linked to carcinogenesis. Ferroptosis—a form of iron-dependent, lipid peroxidation-induced regulated cell death—was discovered. In the development of cancer, it has become an important factor. According to newly available data, ferroptosis regulates tumor growth, and cancer exhibits aberrant m6A levels in crucial ferroptosis regulatory components. On the other hand, m6A has multiple roles in the development of tumors, and the relationship between m6A-modified ferroptosis and malignancies is quite intricate. In this review, we first give a thorough review of the regulatory and functional roles of m6A methylation, focusing on the molecular processes of m6A through the regulation of ferroptosis in human cancer progression and metastasis, which are strongly associated to cancer initiation, progression, and drug resistance. Therefore, it is crucial to clarify the relationship between m6A-mediated regulation of ferroptosis in cancer progression, providing a new strategy for cancer treatment with substantial clinical implications.